Febrile Neutropenia and Indications for Administration of Antibiotics: A Perspective from Pakistan - Hassan Mahmood, Zia Ullah, Bilal Hassan, Asma Kazi, Shehrbano Batool, Faiza Irshad, (Pakistan Journal of Medical & Health Sciences, 2023)
Background & Objectives: The administration of antibiotics within one hour of the patient's presentation is a conventional treatment aim for febrile neutropenia (FN). The objective of this study was to identify what proportion of children diagnosed with FN had a time to antibiotic administration (TTA) of less than one hour and to understand the causes of the delay.. Place of Study: Mayo Hospital Lahore Study Duration: January 2021 to June 2021 Methods: The children who presented with FN were the subject of a prospective investigation. The most significant metric of success was the proportion of patients who were administered antibiotics within one hour after the conclusion of the triage process. The presentation's location, the time of day, and the day of the week are all significant predictive variables. An study was conducted on the causes of the delayed TTA. Results: Evaluations for TTA were performed on a total of 200 children (mean age: 7 years) diagnosed with FN. The primary impact as a result 60% of parents were able to complete the TTA within sixty minutes. The likelihood of a delayed TTA occurred less frequently when patients were examined when the night was still young. Patients who did not have a focus of care had a higher risk of having a delayed TTA. The infection, both during the evaluations that took place in the oncology daycare and those that took place over the weekend, was found in none. Patients who were seen during the daytime or on the weekends had a longer time to treatment than those who presented at the AM or night or weekdays. Interpretation & Conclusions: Antibiotics were administered more quickly to the children who were being monitored for fever. The most significant factors contributing to the delay were admission and the need to await blood levels Keywords: Febrile neutropenia, support care, and delay to antibiotics